Pengaruh Media Sosial dan Event Pariwisata terhadap Minat Kunjung Wisatawan Objek Wisata Danau Situ Tunggilis Desa Situsari Kecamatan Cileungsi Kabupaten Bogor - Turah Slamet; Maudy Alisia Juvoni (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Social Media, Tourism Events on Interest in Visiting Tourists at the Situ Tunggilis Lake Tourism Object, Siteari Village, Cileungsi District, Bogor Regency. The research was conducted on visitors to the Situ Tunggilis Lake Tourism area, Siteari Village, Cileungsi District, Bogor Regency. The sample used in this study amounted to 100 respondents. This study used a purposive sampling technique and data analysis with multiple linear regression. Hypothesis testing uses the T test and F test with the help of the SPSS version 16.0 application program. The results of multiple linear regression indicate that social media has a positive and significant effect on intention to return. Tourism Events have a positive and significant effect on the intention to visit again. Based on the results of the F test, it shows that Social Media and Tourism Events simultaneously have a significant effect on the intention to return. And the coefficient of determination of influence is 70.2%. Keywords: intention to visit, social media, tourism events